Oesophagectomy after definitive chemoradiation in patients with locally advanced oesophageal cancer. - Borghesi, S; Hawkins, M; Tait, D (2008)
AIMS: The clinical benefit of salvage oesophagectomy in patients who recur after radical chemoradiotherapy (CRT) is not clearly defined. This study retrospectively evaluated the outcome in patients who underwent salvage oesophagectomy having failed primary CRT. MATERIALS AND METHODS: Between March 1999 and October 2005, 181 patients with oesophageal cancer were treated at the Royal Marsden Hospital with definitive CRT. Ten patients underwent salvage oesophagectomy. All of them had locally advanced cancer of the oesophagus at presentation (adenocarcinoma in three patients and squamous cell carcinoma in seven patients) and received combined CRT, consisting of 12 weeks of cisplatin and 5-fluorouracil-based chemotherapy followed by CRT. Radiotherapy was delivered with a computed tomography-planned technique to a dose of 54 Gy with daily 5-fluorouracil. RESULTS: An Ivor-Lewis procedure was carried out in all cases. The median time between the end of CRT and surgery was 5 months (range 1-67). Curative resection was achieved in three patients, seven had microscopic positive circumferential margins. One patient died postoperatively and complications occurred in four cases: anastomotic leak in two patients, pneumonia in one patient, empyema and sepsis in one patient. The median critical care unit stay was 7 days (range 4-26) and hospitalisation was 21 days (range 15-84). With a median follow-up period of 45.5 months (range 5-89) the 1-, 2- and 3-year survival calculated from the completion of CRT was 70, 50 and 30%, respectively. Median survival was 21.5 months (range 8-90). CONCLUSIONS: Salvage oesophagectomy may prolong survival in carefully selected patients with local relapse. Patients fit for surgery at presentation benefit from a more intensive follow-up protocol to detect early recurrence.